Investigating the environmental effect of globalization: insights from selected industrialized countries - Aluko, Olufemi Adewale; Opoku, Eric Evans Osei; Ibrahim, Muazu (Academic Press, 2021)
Despite the burgeoning literature on the globalization-environmental degradation nexus, this area of empirical interest is still riddled with ambiguity. Thus, based on an extended Stochastic Impacts by Regression on Population, Affluence and Technology (STIRPAT) model, we re-investigate the effect of globalization on environmental degradation for 27 selected industrialized countries over the period 1991-2016. More specifically, we shed light into how overall globalization and its various components – economic, social and political globalization – affect environmental degradation. We advance existing literature by considering a measurement approach which disaggregates overall, economic, social and political globalization into their de facto and de jure aspects. Using the augmented mean group estimator, we find that overall and economic globalization reduce environmental degradation while social and political globalization do not exert any significant effect on globalization. With respect to the de facto and de jure aspects, we observe that, while only de facto economic globalization mitigates environmental degradation, de jure overall, economic and social globalization also dampen environmental degradation. We provide some policy implications in the end.